Alkaloid chemodiversity in Mandragora spp. is associated with loss-of-functionality of MoH6H, a hyoscyamine 6β-hydroxylase gene - Schlesinger, Daniel (Plant science : an international journal of experimental plant biology, 2019)
Copyright © 2019 Elsevier B.V. All rights reserved.